Industrial Policy Considerations for Structural Change in Peripheral Areas in the 21st Century - Lauxmann, Carolina; Juárez, Javier (Sociedad y Economía, 2024)
This paper examines an ongoing discussion in the field of development studies: the significance of state intervention in promoting industrial sector development to enable viable structural transformation processes within the contemporary capitalist economy. Drawing from a bibliographical survey and content analysis techniques, we begin by tracing the historical evolution of this discourse and subsequently delve into the present-day debate. Within this context, two distinct positions emerge—though not mutually exclusive—highlighting varying degrees of emphasis on the manufacturing sector and state policies aimed at stimulating it for overall development. To deepen our understanding, we analyze recent development experiences, seeking insights into the implemented processes and policies. In conclusion, we emphasize the necessity of designing and implementing policies that encourage manufacturing activity, thereby facilitating structural transformation in the current capitalist landscape.